Effect of zeranol on the performance of guzerá steers grazing on guinea grass alone or on grass/legume - Favoretto, Vanildo; Vieira, Paulo de Figueiredo; Sampaio, Alexandre Amstalden Moraes; Oliveira, Mauro Dal Secco de; Malheiros, Euclides Braga (Pesquisa Agropecuaria Brasileira, 2014)
The purpose of this trial was to evaluate the liveweight gain of steers receiving or not zeranol and grazing three guinea grass pasture: grass alone, grass with nitrogen fertilization, and grass/legume (Panicum maximum/Neonotonia wightii). Guzerá steers with 220 kg of mean liveweight were used. Stocking rates were adjusted according to the put-and-take system. Animals were weighed and the pastures were sampled at 35-day intervals. Daily weight gains were similar in all pastures, whereas gain/hectare increased for guinea grass with nitrogen. Daily weight gain and gain/hectare were 557 g and 394 kg for implanted animals and 466 g and 324 kg for not implanted animals, therefore, animals implanted gained more 1953% for daily weight gain and 21.60% for gain/hectare in all pastures.